Prolonged Effect of Zoledronic Acid on Bone Mineral Density and Turnover in HIV‐Infected Adults on Tenofovir: A Randomized, Open‐Label Study. (24th October 2019) - Carr, Andrew; Kerr, Stephen J; Richardson, Robyn; Ebeling, Peter; Pocock, Nicholas; Rojas, Jhon; Martinez, Esteban; Hoy, Jennifer; ,
ABSTRACT: Zoledronic acid (ZOL) 5 mg annually was more effective than tenofovir disoproxil fumarate (TDF) switching at increasing bone mineral density (BMD) over 24 months in HIV‐infected, osteopenic adults. To determine whether the effects of ZOL would persist without further infusions, we compared changes in left hip and spine BMD over 36 months in participants randomized to ZOL 5 mg at baseline and month 12 (and to continue TDF) or to switch TDF (without receiving ZOL). We also compared changes in the plasma bone turnover markers (BTMs) C‐terminal telopeptide of type 1 collagen (CTX; bone resorption), and procollagen type 1 N propeptide (P1NP; bone formation) and determined whether CTX and P1NP changes at month 3 predicted BMD changes at month 36. Changes were compared in the per‐protocol populations, which included 32 (74%) of 43 participants randomized to ZOL and 37 (88%) of 42 participants who switched TDF. Despite not receiving ZOL after month 12, mean hip and spine BMD change from baseline were stable and remained greater with ZOL at month 36 than with TDF switching (spine: 7.5% versus 2.7%, mean difference 4.7%, p < 0.001; hip: 5.5% versus 1.5%, mean difference 4.0%, p < 0.001). CTX and P1NP levels declined in both groups but significantly more with ZOL. Only percent changes in P1NP at month 3 correlated inversely with BMD changes at month 36 (spine: rho = −0.442, p < 0.001; hip: rho = −0.373, p = 0.002). Two infusions of ZOL (in the presence of ongoing TDF) yielded sustained BMD increases through month 36 that remained greater than with TDF switching. © 2019 American Society for Bone and Mineral Research.